Characteristics of school-based health services associated with students' mental health. Issue 1 (January 2018) - Denny, Simon; Howie, Hamish; Grant, Sue; Galbreath, Ross; Utter, Jennifer; Fleming, Theresa; Clark, Terryann
Objective: School-based health services (SBHS) have been shown to improve access to mental health services but the evidence of their effectiveness on students' mental health is lacking. Our objective was to examine associations between variation in the provision of SBHS and students' mental health. Methods: A cross-sectional analysis of a nationally representative health and well-being survey of 8500 New Zealand high school students conducted in March–November 2012. Students' mental health is related to data on school health services obtained from clinic leaders and clinicians from 90 participating high schools. Results: After adjustment for socio-demographic differences in students between schools, increasing levels of services were associated with progressively lower levels of student-reported depressive symptoms (p = 0.002), emotional and behavioural difficulties (p = 0.004) and suicidality (p = 0.008). Services with greater levels of nursing hours (p = 0.02) and those that performed routine, comprehensive psychosocial assessments (p = 0.01) were both associated with lower levels of student-reported depressive symptoms. Greater levels of nursing hours and doctor hours were associated with lower self-reported suicidality among students. Conclusions: Although a causal association between school-based health services and students' mental health cannot be demonstrated, these findings support the benefit of such services and the need for a cluster randomized trial.